Animal source food consumption and its determinants among children aged 6 to 23 months in sub-Saharan African countries: a multilevel analysis of demographic and health survey - Enyew Getaneh Mekonen (BMC, 2024)
Abstract Introduction Child undernutrition is a major public health problem in sub-Saharan Africa. Children who eat animal-based foods have higher intakes of various nutrients that are important for optimal linear growth. However, the prevalence of animal-source food consumption was low across many countries. Therefore, this study aimed to determine the prevalence of good consumption of animal-source foods and its determinants among children aged 6 to 23 months in sub-Saharan African countries. Methods A cross-sectional pooled dataset using recent demographic and health surveys from 19 sub-Saharan African countries was employed. A total weighted sample of 65,742 children aged 6 to 23 months was included in the study. Data extracted from the recent DHS data sets were cleaned, recorded, and analyzed using STATA/SE version 14.0 statistical software. Descriptive analysis was carried out to present both individual and community-level variables using frequencies and percentages. A multilevel mixed-effects logistic regression was used to determine the factors associated with the outcome variable. Finally, variables with a p-value less than 0.05 and an adjusted odds ratio with a 95% confidence interval were declared statistically significant. Results In this study, 43.1% (95% CI: 42.7-43.5%) of children aged 6 to 23 months consumed animal-source foods. Factors like maternal education [AOR = 1.36; 95% CI (1.28, 1.44)], maternal occupation [AOR = 1.24; 95% CI (1.18, 1.31)], exposure to media [AOR = 1.30; 95% CI (1.24, 1.36)], wealth index [AOR = 1.16; 95% CI (1.10, 1.23)] & [AOR = 1.28; 95% CI (1.21, 1.36)], owned a mobile telephone [AOR = 1.23; 95% CI (1.17, 1.29)], ANC visits [AOR = 1.20; 95% CI (1.15, 1.25)], place of delivery [AOR = 1.09; 95% CI (1.04, 1.14)], PNC checkup [AOR = 1.34; 95% CI (1.28, 1.39)], the current age of the child [AOR = 1.99; 95% CI (1.85, 2.14)], [AOR = 3.34; 95% CI (3.14, 3.56)], & [AOR = 4.3; 95% CI (4.10, 4.66)], birth interval [AOR = 0.92; 95% CI (0.87, 0.97)], residence [AOR = 1.43; 95% CI (1.35, 1.50)], community illiteracy [AOR = 0.91; 95% CI (0.86, 0.96)], and community poverty [AOR = 1.07; 95% CI (1.01, 1.14)] were significantly associated with consumption of animal-source foods. Conclusion Less than half of children aged 6 to 23 months consumed any type of animal-source foods in sub-Saharan African countries. Higher educational level, non-agricultural work, exposure to media, high economic status, having a mobile telephone, attending 4 + ANC visits, health facility delivery, PNC checkups, older children, a birth interval of 24 months, urban residency, community literacy, and low community poverty were determinates of good consumption of animal source foods. Women empowerment, dissemination of nutrition-related information through mass media, promotion of health facility delivery, and improving utilization of maternal health services are recommended to improve infant and child feeding practices.